The shadow riders - L'Amour, Louis, 1908-1988 (L'Amour, Louis, 1908-1988. Louis L'Amour collection., 1982)
Soldiers on opposite sides in the Civil War, Dal and Mac Traven must join forces to defeat their longtime rivals, a ruthless band of killers whose reign of death and pillage extends south of the border.